Design and Implementation of Network Security Systems on Virtualized Networks - Akmal Baharuddin Syam; Rakhmadi Rahman (ITEJ (Information Technology Engineering Journals), 2024)
This report, entitled "Design and Implementation of Network Security Systems on Virtualized Networks," was prepared to fulfill the final assignment of the Network Security course at the Bacharuddin Jusuf Habibie Institute of Technology (ITH). This research aims to design, implement and identify network security vulnerabilities in a virtualization environment using Proxmox Virtual Environment (Proxmox VE) in VirtualBox. The research results show that Proxmox VE in VirtualBox is less successful in optimizing software-hardware resources by implementing security mechanisms such as firewalls, encryption, IDS/IPS, VPN, and IAM. Even though it has several shortcomings, Proxmox VE has proven to be effective in managing virtual networks safely and efficiently when carried out outside of VirtualBox. This research also provides practical experience for students in implementing and identifying network security vulnerabilities, preparing them for real-world challenges.